Argentate(i) and (iii) complexes as intermediates in silver-mediated cross-coupling reactions. Issue 40 (30th April 2018) - Weske, Sebastian; Hardin, Richard A.; Auth, Thomas; O'Hair, Richard A. J.; Koszinowski, Konrad; Ogle, Craig A.
Abstract : Silver-mediated cross-coupling reactions proceed via anionic ate complexes, which have been characterized by a combination of NMR spectroscopy, ESI mass spectrometry, and quantum-chemical calculations. Abstract : Despite the potential of silver to mediate synthetically valuable cross-coupling reactions, the operating mechanisms have remained unknown. Here, we use a combination of rapid-injection NMR spectroscopy, electrospray-ionization mass spectrometry, and quantum chemical calculations to demonstrate that these transformations involve argentate(i ) and (iii ) complexes as key intermediates.